2014
DOI: 10.1186/1476-069x-13-20
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility and use of urban green spaces, and cardiovascular health: findings from a Kaunas cohort study

Abstract: BackgroundThe aims of this study were to explore associations of the distance and use of urban green spaces with the prevalence of cardiovascular diseases (CVD) and its risk factors, and to evaluate the impact of the accessibility and use of green spaces on the incidence of CVD among the population of Kaunas city (Lithuania).MethodsWe present the results from a Kaunas cohort study on the access to and use of green spaces, the association with cardiovascular risk factors and other health-related variables, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
163
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(198 citation statements)
references
References 37 publications
8
163
2
5
Order By: Relevance
“…When stratified by gender and degree of urbanization, there was a tendency for slightly stronger associations between green spaces and health for women and those living in non-densely populated areas, but this was not statistical significant. The small differences we found by gender are consistent with previous findings that have suggested that women use green spaces more because they are more likely to take care of older people and children than men (Tamosiunas et al, 2014). However, some other studies have found that green spaces are more used and more beneficial for males (Richardson and Mitchell, 2010).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…When stratified by gender and degree of urbanization, there was a tendency for slightly stronger associations between green spaces and health for women and those living in non-densely populated areas, but this was not statistical significant. The small differences we found by gender are consistent with previous findings that have suggested that women use green spaces more because they are more likely to take care of older people and children than men (Tamosiunas et al, 2014). However, some other studies have found that green spaces are more used and more beneficial for males (Richardson and Mitchell, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…There is some evidence suggesting that the associations between natural outdoor environments and health might be stronger for low socioeconomic statuses (SES) (Mitchell and Popham, 2007;De Vries et al, 2003;Mitchell and Popham, 2008;Dadvand et al, 2014), and might vary by gender (Tamosiunas et al, 2014;Reklaitiene et al, 2014;Astell-Burt et al, 2014;Richardson and Mitchell, 2010) and degree of urbanization (Mitchell and Popham, 2007;De Vries et al, 2003). But these differences are still not well-established.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, green space has been associated a number of beneficial health effects (Lee and Maheswaran, 2010;Hartig et al, 2014) including decreased mortality and longevity (Mitchell and Popham, 2008;Gascon et al, 2016), decreased cardiovascular disease (Pereira et al, 2012;Tamosiunas et al, 2014), improved people's self-reported general health (Maas et al, 2006;de Vries et al, 2013) and mental health (Gascon et al, 2015), reduced behavioral problems (Amoly et al, 2014) and increased cognitive function in children, better sleep patterns (Astell-Burt et al, 2013), recovery from illness (Ulrich, 1984), social contacts (Maas et al, 2009;de Vries et al, 2013), the microbiome (Hanski et al, 2012) and improved birth outcomes (Dzhambov et al, 2014). Increased physical activity and social contacts, psychological restoration/stress reduction, and a reduction in environmental exposure such as noise and air pollution and temperature have been proposed as possible mechanisms for the health benefits of green space (Lee and Maheswaran, 2010;Hartig et al, 2014;de Vries et al, 2013).…”
Section: Cars-related Environmental Exposure and Healthmentioning
confidence: 99%
“…Recent epidemiological studies seem to confirm the beneficial health impact of natural spaces. Demonstrated health effects in a general population are, for example, reduced mortality (Gascon et al 2016), reduced cardiovascular morbidity (Tamosiunas et al 2014;Donovan et al 2015), lower blood pressure ) and decreased depressive symptoms (Reklaitiene et al 2014). At the same time, improved conditions are found for pregnancy outcomes (Dadvand et al 2012), and general physical and mental health (Annerstedt et al 2012;TrigueroMas et al 2015).…”
Section: Health Effects As Co-benefits Of Nature-based Solutions To Cmentioning
confidence: 99%